lecture4

lecture4 - Economics 2: Growth (Solow Model II & III) c...

Info iconThis preview shows pages 1–8. Sign up to view the full content.

View Full Document Right Arrow Icon
Economics 2: Growth c ± Kumar Aniket Lecture 4, Week 7 c ± Kumar Aniket Economics 2: Growth (Solow Model II & III)
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Solow Model - II Definition (Solow Model II) The most basic Solow model with positive population growth and no technological progress. c ± Kumar Aniket Economics 2: Growth (Solow Model II & III)
Background image of page 2
Solow Model - II Definition (Solow Model II) The most basic Solow model with positive population growth and no technological progress. Assumption a) Positive population growth Δ L L = n > 0 c ± Kumar Aniket Economics 2: Growth (Solow Model II & III)
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Solow Model - II Definition (Solow Model II) The most basic Solow model with positive population growth and no technological progress. Assumption a) Positive population growth Δ L L = n > 0 b) no technological progress Δ A A = 0 c ± Kumar Aniket Economics 2: Growth (Solow Model II & III)
Background image of page 4
CRS Production Function Y = F ( K , L ) Constant Returns to Scale Production Function λ Y = F ( λ K , λ L ) where λ = 1 L Per Worker Production Function y = f ( k ) where y = Y L , k = K L c ± Kumar Aniket Economics 2: Growth (Solow Model II & III)
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Growth Rate of Capital Per Worker k t = K t L t Δ k t k t = Δ K t K t - Δ L t L t gr ( k t ) = gr ( K t ) - gr ( L t ) c ± Kumar Aniket Economics 2: Growth (Solow Model II & III)
Background image of page 6
k t = K t L t Δ k t k t = Δ K t K t - Δ L t L t gr ( k t ) = gr ( K t ) - gr ( L t ) Δ K t K t = Δ k t k
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 8
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 12/21/2011 for the course ECON 3014 taught by Professor Michaelshaw during the Spring '11 term at HKU.

Page1 / 23

lecture4 - Economics 2: Growth (Solow Model II & III) c...

This preview shows document pages 1 - 8. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online